Effect of intervention delivered by lay maternal care providers to improve outcome and parenting skills among adolescents with perinatal depression in Nigeria (the RAPiD study): a cluster randomized controlled trial (2022)
Background: Perinatal depression is more common and is associated with greater negative consequences among adolescents than adults. Psychosocial interventions designed for adults may be inadequate at addressing the unique features of adolescent perinatal depression. Methods: In a two-arm parallel cluster randomized trial conducted in thirty primary maternal care clinics in Ibadan, Nigeria (15-intervention and 15-control) we compared age-appropriate intervention consisting of problem-solving therapy, behavioral activation, parenting skills training, and parenting support from a self- identified adult to care as usual. Pregnant adolescents (aged <20 years) at fetal gestational age16–36 weeks with moderate to severe depression were recruited. Primary outcomes were depression symptoms (Edinburgh Postnatal Depression Scale, EPDS) and parenting practices (Infant-Toddler version of the Home Inventory for Measurement of the Environment, HOME-IT) at six-months postnatal. Results: There were 242 participants (intervention arm: 141; Control arm: 101), with a mean age of 18∙0 (SD- 1∙2). Baseline mean EPDS score was 14∙2 (SD-2.1); 80∙1 % completed the six-month postnatal follow-up. The intervention group had lower level of depressive symptoms than the control group, mean EPDS scores: 5∙5 (SD- 3∙6) versus 7∙2 (SD-4∙0) (adjusted mean difference -1∙84 (95%CI- 3∙06 to 􀀀0∙62; p =0∙003) and better parenting practices, mean total HOME-IT scores: 29∙8 (SD-4∙4) versus 26∙4 (SD-4∙2) (adjusted mean difference 3∙4 (95%Cl- 2∙12 to 4∙69, p =0∙001). Limitations: This study explored the effect of complex interventions making it difficult to know precisely what aspects produced the outcomes. Conclusions: An age-appropriate psychosocial intervention package holds promise for scaling up care for adolescents with perinatal depression especially in resource-constrained settings.